2019
DOI: 10.1177/1060826519829908
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Perinatal Mental Health: At-Risk Fathers’ Perceptions of Help-Seeking and Screening

Abstract: Given the prevalence of paternal perinatal mental health concerns, researchers have suggested introducing routine screening. However, little is known about the acceptability of perinatal screening measures in male populations. Furthermore, the need for screening is influenced by men’s perinatal help-seeking behaviors. A thematic analysis of interview data from nine men at risk of paternal perinatal depression and/or anxiety investigated both acceptability of screening and help-seeking behaviors. Themes indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…As shown in Table 2 , all of the 20 studies addressing acceptability were from high-income Westernized countries. Parent perspectives were reported in eight studies ( 34 , 49 , 78 – 83 ); nine reported health professional perspectives ( 84 92 ); none included both. A further three feasibility and implementation studies reported behavioral indicators (e.g., completion rates) without collecting participants' perspectives ( 93 95 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Table 2 , all of the 20 studies addressing acceptability were from high-income Westernized countries. Parent perspectives were reported in eight studies ( 34 , 49 , 78 – 83 ); nine reported health professional perspectives ( 84 92 ); none included both. A further three feasibility and implementation studies reported behavioral indicators (e.g., completion rates) without collecting participants' perspectives ( 93 95 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a further three studies where assessment had not been introduced into practice, fathers were asked to complete specific measures and comment on their acceptability within a research context. This included the EPDS completed away from clinical environments (e.g., home) ( 79 , 83 ), and the CES-D ( 82 ) and IES-R ( 82 ), which were completed in a NICU but as a research questionnaire.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with past research, our finding suggests that many fathers may feel alienated from effective support. In prior research fathers report not seeking support because of reasons including a belief that the focus should be on the mother and infant in the postnatal period (89), past negative experiences when asking for help (90,91), stigma attached to revealing emotions and vulnerability (92,93) and rigid adherence to masculine values of stoicism and self-reliance (90,94).…”
Section: Discussionmentioning
confidence: 99%